Chapter «Stilo... memoriaeque mandavi»: Two and a Half Conspiracies. Auctors, Actors, Confessions, Records, and Models - Shanzer, Danuta (Reti Medievali E-Book, 2022)
Conspiracies frustrate contemporaries, historiographers, and historians. This article explores roles, focalization, and confession in three conspiracies related to Italy, from the 6th, 4th, and 9th centuries respectively. The protagonists include Boethius, Silvanus, and Theodulf of Orléans. The main contribution is a philological and historiographical re-evaluation of Theodulf's role in the revolt of Bernard of Italy against Louis the Pious (817/18), arguing that Theodulf advised Louis about the punishment of the conspirators. Boethius first emerges as a historico-political exemplum (though his Cons.) in Modoin's rescriptum (Theodulf, C. 73 [820/21]).